Exploring Student Attitudes during Physical Education Class - Ari Wibowo Kurniawan; Rama Kurniawan; Devi Kumala Sari (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aimed to assess the student's attitude in attending physical, sports, and health education. The observed attitude involved their attitude of religion, honesty, discipline, responsibility, politeness, caring (tolerance-mutual cooperation), and confidence. The research was conducted using non-experimental quantitative analysis. This study involved 296 students in SMP Negeri 9 Malang City that consisted of 93 students from class VII, 100 students from class VIII, and 103 students from class IX.  The data were collected through observation, self-assessment sheets, and peer-assessment sheets. Research instruments were analyzed using validity and reliability analysis. From the results of the validity analysis, 15 statements were declared valid. The results of the reliability analysis, the observation guide, self-assessment sheet, and peer-to-peer assessment sheet attained reliability scores of 0.788, 0.790, and 0.811. to obtain research results, analysis using percentages is carried out by researchers. The study results show that students' attitudes are generally classified as excellent with a great culture. Besides, attention and support from the surrounding environment are observed to be very influential for the student's attitude. Stakeholders should facilitate students to develop their behavior and attitudes.